Sistem Pendukung Keputusan Pencarian Universitas di Malang Menggunakan Weight Product dengan Pembobotan Weighted Sum Model - Wahyu Adi Kurniawan (Jurnal Ilmiah Informatika, 2019)
Decision Support System (DSS) is a system that can help someone in making a decision to solve a problem. Weighted Sum Model (WSM) method and Weighted Product (WP) method are used in this system. The WSM method is the sum of the attribute rating multiplications with attribute weights. In this system, WSM method is used as a weight and will be used on the WP method. This weight is filled manually by the user and then calculated by the WSM method. Whereas the Weighted Product (WP) method is a method that uses multiplication to connect attribute ratings, and the rating must be raised first with the weight of the attribute. This system is used in the selection of college in the city of Malang. In the search process there are several criteria used, namely the number of computer department, tuition fees, campus environment, the number of scholarship programs and accreditation. These criteria are used as a reference for college grades used in the assessment section. The search procedure start when a user enters a criteria value that has been determined by the user. Furthermore, the value of the calculation is compared with the value already on data pattern. To find out whether the chosen university matches with the entered criteria, weight of criteria must be checked based on the university chosen by the user. The conversion value from input are compared by the value in the pattern data. The testing process in this study is by using a confusion matrix. Based on testing using the method confusion matrix, researchers obtained 72.50 % value of accuracy, 82,76% value of precision, 80% value of recall and 81,36% value of f-measure.